10 weeks of heavy strength training improves performance-related measurements in elite cyclists - Rønnestad, B. R.; Hansen, J.; Nygaard, H. (Journal of Sports Sciences, 2014)
Elite cyclists have often a limited period of time available during their short preparation phase to focus on development of maximal strength; therefore, the purpose of the present study was to investigate the effect of 10-week heavy strength training on lean lower-body mass, leg strength, determinants of cycling performance and cycling performance in elite cyclists. Twelve cyclists performed heavy strength training and normal endurance training (E&S) while 8 other cyclists performed normal endurance training only (E). Following the intervention period E&S had a larger increase in maximal isometric half squat, mean power output during a 30-s Wingate sprint (P < 0.05) and a tendency towards larger improvement in power output at 4 mmol/L [la-] than E (P = 0.068). There were no significant difference between E&S and E in changes in 40-min all-out trial (4 ± 6% vs. -1 ± 6%, respectively, P = 0.13). These beneficial effects may encourage elite cyclists to perform heavy strength training and the short period of only 10 weeks should make it executable even in the compressed training and competition schedule of elite cyclists.